Vietnam protest theatre the television war on stage - Alter, Nora M. 1962- (Indiana Univ. Press, 1996)
The escalation of the war in Vietnam in the mid-1960s unleashed worldwide protest. Playwrights grappled with the complexities of post-imperialist politics and the problems of creating effective political theatre, and for much of their audience the war was chiefly an event on the evening news. The ephemeral theatre these writers created, today little-known and rarely studied, provides an important window on a complex moment in culture and history.
Keywords: Geschichte 1900-2000; Geschichte 1965-1975; Toneelstukken; Toneelvoorstellingen; Vietnam-oorlog; Drama; Vietnamkrieg; Drama -- 20th century -- History and criticism; Vietnam War, 1961-1975 -- Literature and the war; Politisches Theater; Theater; Literatur; Protestbewegung